Recognizing the long-term sequelae of burns as a chronic medical condition. Issue 2 (March 2020) - Kelter, B.M.; Holavanahalli, R.; Suman, O.E.; Ryan, C.M.; Schneider, J.C.
Abstract: As medicine continues to advance, many individuals are living longer with injuries previously considered life threatening. These individuals often face numerous long-term physical and psychological sequelae associated with their injury that persist through the course of their lives. Recently, other injury populations have begun to think of their condition as "chronic". Using data collected from the Burn Model System National Database, a framework for the reconsideration of burn injury as a chronic condition is proposed.